Spotlight and Criticism of Islamic Religious Education in Schools - Fajrussalam, Hisny; Ruswandi, Uus; Arifin, Bambang Samsul (CV. Creative Tugu Pena, 2021)
Historically, Islamic religious education was an education developed by the colonial government. Over time, the government continues to issue policies to provide direction for national development and the development of Islamic Islamic Studies for Muslim communities in Indonesia. Meanwhile, schools are a means and a place to study for students, as well as a place to enrich and expand the knowledge of students, especially Islamic Education. However, PAI which is currently being taught in schools in Indonesia is not without problems. This research tries to find the problem. The research method used is literature study. The results showed that the obstacles faced by PAI in schools today are students, the learning environment, teacher competence and learning methods. Keywords: Islamic Religious Education, Criticism of Islamic Religious Education, Islamic Education